Effects of collagen and chondroitin sulfate on relaxation at multiple magnetic field strengths - Olli-Pekka Aro; Victor Casula; Nina E. Hänninen; Jouni Karjalainen; Mikko J. Nissi; Miika T. Nieminen; Henning Henschel (Heliyon)
Purpose: To elucidate the connection between MRI relaxation properties of articular cartilage and tissue composition, in terms of collagen and chondroitin sulfate (CS). Additional aims were to determine the effect of different magnetic field strengths, as well as the effect of concentrations of the components on relaxation properties. Methods: A series of MRI phantoms consisting of gels containing collagen and chondroitin sulfate were prepared with final concentrations of collagen in the range 20-60 mg/g and the CS concentration in the range 0-40 mg/g. R1 (= 1/T1) and R2 (= 1/T2) values of the phantoms were measured at three different MRI field strengths (1.5, 3.0 and 9.4 T), R1ρ (= 1/T1ρ) values were measured at 9.4 T. Results: Relaxation rates generally increased with increasing concentration of either of the compounds. R1 values generally increased with CS, and at clinically used magnetic fields, namely 1.5 T and 3.0 T, with collagen concentration. At 9.4 T, R2 values also showed an increase with collagen concentration that could not be clearly identified at lower field strengths. R1ρ values increased with both collagen and CS concentration but the amplitude of the spin-lock pulse only had a limited effect on relaxation rates above 100 Hz. Conclusions: Our results suggest that R1, R2, and R1ρ are modulated by collagen and CS concentrations, with collagen likely dominating at physiological concentrations.